2020
DOI: 10.1097/md.0000000000022086
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency catheter ablation in a patient with dextrocardia, persistent left superior vena cava, and atrioventricular nodal reentrant tachycardia

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…Routine visualization includes echocardiography, cardiac CT, and 3D mapping. For situs solitus and situs inversus without an additional abnormal anatomy, adjusting for projection angulation and catheter manipulation provides an efficient solution to achieve successful catheter ablation 25,26 . For patients with a complicated anatomy, management entails routine visualization and 3D reconstruction to comprehend the distorted cardiac structure and guide the positioning of the catheter which eventually reduces the procedural duration, minimizes risks of complications from the procedure, and facilitates acute success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Routine visualization includes echocardiography, cardiac CT, and 3D mapping. For situs solitus and situs inversus without an additional abnormal anatomy, adjusting for projection angulation and catheter manipulation provides an efficient solution to achieve successful catheter ablation 25,26 . For patients with a complicated anatomy, management entails routine visualization and 3D reconstruction to comprehend the distorted cardiac structure and guide the positioning of the catheter which eventually reduces the procedural duration, minimizes risks of complications from the procedure, and facilitates acute success.…”
Section: Discussionmentioning
confidence: 99%
“…For situs solitus and situs inversus without an additional abnormal anatomy, adjusting for projection angulation and catheter manipulation provides an efficient solution to achieve successful catheter ablation. 25,26 For patients with a complicated anatomy, management entails routine visualization and 3D reconstruction to comprehend the distorted cardiac structure and guide the positioning of the catheter which eventually reduces the procedural duration, minimizes risks of complications from the procedure, and facilitates acute success. In our study, the paucity of 3D mapping and 3D reconstruction caused the failure of three cases, one of which was complicated by an acute tamponade arising from penetration into the aorta.…”
Section: Routine Visualization and Three-dimensional Reconstruction I...mentioning
confidence: 99%
“…The key point to a successful ablation in patients with dextrocardia is understanding the heart’s anatomical structure nd the great vessels and identifying a strategy before conducting the operation. Relevant literature reported that the femoral vein is the most common ablation pathway in supraventricular tachycardia patients with dextrocardia when needed to RFCA ( 14 , 15 ). In some cases, the superior vena cava is also the venous access to the heart ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Arrhythmias are usually treated with antiarrhythmic medications and patients without adequate control are subjected to catheter ablation procedures (cryoablation or radiofrequency (RF) ablation). The feasibility of catheter ablation procedures for atrial fibrillation/flutter [ 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ], supraventricular tachycardia [ 101 , 102 , 103 ], including AVRT [ 101 ] and WPW syndrome [ 104 ], was demonstrated. Patients with an interrupted inferior vena cava should undergo the procedure using the jugular venous approach.…”
Section: Management Of Cardiac Malposition Patients During Adulthoodmentioning
confidence: 99%